Internship Program to Enhance Youth Development: Learning from the Real World - Fakhruddin Fakhruddin; Bunyamin Bunyamin; Liliek Desmawati; Wirathep Pathumcharoenwattana; Yudi Siswanto (Journal of Nonformal Education, 2023)
One of the issues encountered in youth development field involves identifying prospective management. The research aims to analyze the internship program on the youth to enhance their development through academic and non-academic achievements. Also to describe the impacts of the internship programs in the youth development. The research method use the mixed method with 100 youth’s from State University Semarang as the sample participants. The research collecting data uses a structured questionnaire with a modified scale applied for academic and non-academic achievements. The research result shows that the Internship Program can improve youth achievements both at academic and non-academic levels. This program provides opportunities for the youth to collaborate and work with other roles in the real world. Conversely, this program can improve the youth's achievements at academic and non-academic levels. The research result shows that the sig value = 0,000 0,05 while the t-test value is 38,756. The internship program provides benefits to youths who participate in the program. Otherwise, Internship partners who open the opportunities for the youth to gain experiences also receive benefits for workplace experience. This research will give the novelty on the latest standards to held the internship program that can enhance youth development.